2013
DOI: 10.3390/geosciences3010063
|View full text |Cite
|
Sign up to set email alerts
|

Rocks, Clays, Water, and Salts: Highly Durable, Infinitely Rechargeable, Eminently Controllable Thermal Batteries for Buildings

Abstract: Materials that store the energy of warm days, to return that heat during cool nights, have been fundamental to vernacular building since ancient times. Although building with thermally rechargeable materials became a niche pursuit with the advent of fossil fuel-based heating and cooling, energy and climate change concerns have sparked new enthusiasm for these substances of high heat capacity and moderate thermal conductivity: stone, adobe, rammed earth, brick, water, concrete, and more recently, phase-change m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…When high thermal mass materials are used in buildings, passive sensible storage is the technology that allows the storage of high quantity of energy, giving thermal stability inside the building. Materials typically used are rammed earth, alveolar bricks, concrete, or stone [30].…”
Section: Passive Technologiesmentioning
confidence: 99%
“…When high thermal mass materials are used in buildings, passive sensible storage is the technology that allows the storage of high quantity of energy, giving thermal stability inside the building. Materials typically used are rammed earth, alveolar bricks, concrete, or stone [30].…”
Section: Passive Technologiesmentioning
confidence: 99%
“…Rempel and Rempel [5] did a very interesting comparison of different thermal mass systems (authors call them passive systems), comparing mainly rocks, clays, water and salts. The authors showed that while passive systems cannot provide the instant heating or cooling of a mechanical switch, they are nevertheless highly adjustable by variation of material, thickness, and configuration, and therefore can be refined to meet the occupant needs.…”
Section: High Thermal Mass Materialsmentioning
confidence: 99%
“…Heat fluxes across outdoor (left axis) and indoor (right axis) surfaces of exterior walls on a typical sunny January day in Denver, Colorado[5].…”
mentioning
confidence: 99%
“…In upland environments marked by dramatic fluctuations of climate, the protected and long-lasting edifices of semi-subterranean housing can maintain relatively stable interior temperatures due to the thermal "flywheel" effect: the soil and stone surrounding the lived space absorb and release the sun's energy at a relatively slow rate, thus tempering the effect of dramatic temperature change (5). As thermally rechargeable materials, the basalt blocks that lined Tsaghkahovit's earthen dugouts were continuously at work, intercepting and storing solar energy and returning that heat to their surroundings at cooler times thanks to their vibrant mineralogies, densities, and emissivities (Rempel and Rempel 2013). In general, underground living underscores the ways in which humans habituate to the challenges of extreme mountain zones, and explanations for the unique semi-subterranean houses of the Armenian highland often rest on the affordances of their thermal properties (e.g.…”
Section: Architectur Al Affiliatesmentioning
confidence: 99%